1988
DOI: 10.1080/03014468800009471
|View full text |Cite
|
Sign up to set email alerts
|

Secondary sexual development of ‘Cape Coloured’ girls following kwashiorkor

Abstract: This report describes the secondary sexual development of 45 'Cape Coloured' female ex-kwashiorkor patients and 43 female controls. All patients were originally seen between five months and four years four months of age, treated and then followed up for 15 years after discharge. Age at menarche was available on 42 ex-patients and 33 controls, and age at peak height velocity (PHV) was available for 30 ex-patients and 15 controls. Maximum likelihood estimates of the mean age at entry to each pubertal stage were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
10
1
Order By: Relevance
“…6,7 Information on environmental factors including previous nutrition, body fat or size, and race are important in studies of puberty timing. Early severe protein-energy malnutrition presenting as marasmus (severe wasting and growth retardation as a result of insufficient intake) but not kwashiorkor (edematous protein-deficiency malnutrition) delays timing of puberty, at least in girls, [48][49][50] and chronic malnutrition during childhood through to puberty retards pubertal development in boys and girls. 51 Among chronically undernourished children, age at menarche was delayed by ϳ2 years among the girls and sexual maturity measures were delayed by ϳ3 years in boys.…”
Section: Issues In Secular Trend Analysis For Pubertal Timing Studiesmentioning
confidence: 99%
“…6,7 Information on environmental factors including previous nutrition, body fat or size, and race are important in studies of puberty timing. Early severe protein-energy malnutrition presenting as marasmus (severe wasting and growth retardation as a result of insufficient intake) but not kwashiorkor (edematous protein-deficiency malnutrition) delays timing of puberty, at least in girls, [48][49][50] and chronic malnutrition during childhood through to puberty retards pubertal development in boys and girls. 51 Among chronically undernourished children, age at menarche was delayed by ϳ2 years among the girls and sexual maturity measures were delayed by ϳ3 years in boys.…”
Section: Issues In Secular Trend Analysis For Pubertal Timing Studiesmentioning
confidence: 99%
“…These data have been made available to the present authors who have already reported on the timing and magnitude of adolescent growth in height and weight and secondary sexual development of the females of the sample (Cameron, Moodie, Mann and Hansen 1985, Cameron, Jones, Mitchell, Moodie, Bowie, Mann and Hansen, 1986, Cameron et al 1988). This paper reports on the timing and pattern of secondary sexual development in boys of the same sample.…”
Section: Introductionmentioning
confidence: 84%
“…The ex-patients and controls have been described in detail by Keet, Moodie, Wittmann and Hansen (1971) and by Cameron et al (1986Cameron et al ( , 1988. Briefly, 221 patients between the ages of 5 months and 4 years 4 months were originally treated for kwashiorkor.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations